2020
DOI: 10.1111/psyg.12517
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 12‐month exercise intervention on physical and cognitive functions of nursing home residents requiring long‐term care: a non‐randomised pilot study

Abstract: Aims We performed a 12‐month exercise intervention for ‘nursing home for the elderly’ residents requiring long‐term care. We evaluated changes in their muscular strength, muscle mass, and cognitive function. Methods Thirty‐seven nursing home residents (Mini‐Mental State Examination (MMSE): 14.7 ± 7.0, Barthel Index: 44.2 ± 18.9) were enrolled. We divided the participants into the exercise intervention group (n = 19) and non‐intervention group (n = 18) ensuring no significant difference in the participants' cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…The results revealed that, compared with single interventions, multifaceted interventions produced better outcomes for the improvement of physical function and muscle strength. Tsugawa et al ( 2020 ) studied the cognitive status of older care home residents in relation to exercises; the results indicated that the exercise can effectively improve the cognitive function of care home residents in need of long‐term nursing. Currently, the number of studies on frailty in patients with schizophrenia is limited.…”
Section: Discussionmentioning
confidence: 99%
“…The results revealed that, compared with single interventions, multifaceted interventions produced better outcomes for the improvement of physical function and muscle strength. Tsugawa et al ( 2020 ) studied the cognitive status of older care home residents in relation to exercises; the results indicated that the exercise can effectively improve the cognitive function of care home residents in need of long‐term nursing. Currently, the number of studies on frailty in patients with schizophrenia is limited.…”
Section: Discussionmentioning
confidence: 99%